Using Two-Eyed Seeing to Codevelop First Nations Housing Policies with Canada - McDougall Sack, Tiffany (Journal of Aboriginal Economic Development, 2025)
This study explores the use of Two-Eyed Seeing to guide the codevelopment of housing policies between First Nations and Canada, fostering meaningful collaboration and advancing self-determination. It examines historical contexts, challenges, and benefits, using interviews with Kitigan Zibi Anishinabeg, Quebec, and Potlotek, Nova Scotia, as case studies. Key principles for effective policy codevelopment include meaningful engagement, respectful dialogue, shared decision-making, and the recognition of Indigenous rights and sovereignty. The paper contributes to ongoing discourse on Indigenous governance and equitable partnerships.